2011
DOI: 10.1108/03321641111152649
|View full text |Cite
|
Sign up to set email alerts
|

The stand for determining of thermal‐electrical material properties of induction heated charge

Abstract: Purpose -The purpose of this paper is to investigate the efficiency of indirect determining of the thermal and electrical material characteristics of induction heated charges. Design/methodology/approach -In the paper, the indirect method based on comparing the experimental and simulation results of temperature distribution has been considered. An influence of the type of the optimization techniques and the objective function form on its effectiveness was analysed. The experimental stand used in the described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…The investigations showed that on the same laboratory setup (for the same sample), it is possible to use effectively (theoretically up to 2 per cent of uncertainty) the TDoT method to determine the specific heat of a charge in a wide range of its changeability. The results obtained can be used to estimate thermal properties of a charge or, in connection with the estimation of electrical parameters, the method can be applied in more complex and precise determination procedures, such as those presented in Zgraja (2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The investigations showed that on the same laboratory setup (for the same sample), it is possible to use effectively (theoretically up to 2 per cent of uncertainty) the TDoT method to determine the specific heat of a charge in a wide range of its changeability. The results obtained can be used to estimate thermal properties of a charge or, in connection with the estimation of electrical parameters, the method can be applied in more complex and precise determination procedures, such as those presented in Zgraja (2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature (Parker et al, 1961;Cieślak and Zgraja, 2014;Seog-Kwang and Yong-Jin, 2007;Clark and Taylor, 1975;Shinzato and Baba, 2001;Hay et al, 2013;Salazar et al, 2008), you can find many methods for determining thermal parameters of the material. However, there is limited information (Zgraja, 2011) about such methods of determining these parameters which could be used directly on the stand of induction heating, even with using their power sources (inverter). In reality, such an approach boils down to solving an inverse problem, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, growing technological requirements increasingly lead to the need for precise, reliable information about the properties of the processed material, which leads to the need to verify them in situ. The importance of the problem raised is confirmed by numerous publications [2][3][4][5][6][7][8][9][10][11], in which the issue of the possibly simplest and quickest way to determine material properties is considered, preferably several at once using one measurement station. The cited literature examples mainly concern attempts to determine thermal properties, that is, thermal diffusivity and volumetric heat capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Reconstruction based on neural networks can be found in Celorrio et al (2010). More approaches are summarized and compared in Tarantola (2005), while Gelin and Ghouati (1996), Zgraja (2011) and Hernandez et al (2011) are aimed at their determining the areas of strain and stress mechanics, electro-heating and other disciplines, respectively.…”
Section: Introductionmentioning
confidence: 99%